SPERM QUALITY IN ADULT MALE RATS EXPOSED TO CADMIUM IN UTERO and LACTATION - Banzato, Thais Petrochelli [UNESP]; Godinho, Antonio Francisco [UNESP]; Mathias da Silva Zacarin, Elaine Cristina; Perobelli, Juliana Elaine; Fernandez, Carla Dal Bianco; Alves Favareto, Ana Paula; Kempinas, Wilma de Grava [UNESP] (Taylor & Francis Inc, 2012)
Recent studies indicate that several anomalies of the male reproductive system may be produced by acute or chronic exposure to chemical substances released into the environment, attributed to increased industrial development. Among these substances are trace metals such as cadmium (Cd). The aim of this study was to assess reproductive parameters in adult male rats whose mothers were exposed to Cd during pregnancy and lactation. For this, pregnant rats were divided into two experimental groups: treated rats, which received ad libitum cadmium acetate (CdAc) solution in distilled water (10 mg Cd/L), and control rats, which received sodium acetate (NaAc) solution in distilled water (equimolar to the CdAc). The results showed that the exposure to Cd in utero and through lactation adversely affected sperm quality of adult rats, as evidenced by compromised sperm morphology and motility and increased rate of cell death in testis.